Composition for forming a coating and method of using the same to manufacture separators for electrochemical devices

CN123036349APending Publication Date: 2026-11-03LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580024076.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-08-22
Filing Date
2025-08-26
Publication Date
2026-11-03

AI Technical Summary

Benefits of technology

[0021]根据本公开的用于形成涂层的组合物包含具有约200,000 g/mol至500,000 g/mol的重均分子量的聚丙烯酸(PAA)作为分散剂,并且因此具有能够形成薄膜涂层的优点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123036349A_ABST
    Figure CN123036349A_ABST
Patent Text Reader

Abstract

The present invention relates to a composition for forming a coating layer used in manufacturing a separator for an electrochemical device; and a method of manufacturing a separator for an electrochemical device using the same. The composition for forming a coating layer has excellent dispersibility by including polyacrylic acid (PAA) having a weight average molecular weight of 200,000 g / mol to 500,000 g / mol, and thus, a thin film coating layer can be manufactured by the method of manufacturing a separator for an electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application is based on and claims priority to Korean Patent Application No. 10-2024-0128230 filed with the Korean Intellectual Property Office on September 23, 2024, and Korean Patent Application No. 10-2025-0117575 filed with the Korean Intellectual Property Office on August 22, 2025, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0002] This disclosure relates to compositions for forming coatings, and methods for using the same to manufacture separators for electrochemical devices. Background Technology

[0003] Electrochemical devices convert chemical energy into electrical energy through electrochemical reactions, and in recent years, lithium secondary batteries, which have high energy density, high voltage, long cycle life, and can be used in various fields, have been widely used.

[0004] Lithium-ion batteries generate electricity through a chemical reaction in which lithium ions move between the positive and negative electrode materials. When lithium ions from the positive electrode move to the negative electrode, the battery is charged, and when lithium ions from the negative electrode return to the positive electrode, energy is released and the battery is discharged. This requires an electrolyte to serve as the path for lithium ions to move between the positive and negative electrodes, and a separator to prevent the positive and negative electrodes from contacting each other. Typically, the four components of a lithium-ion battery are the positive electrode material, the negative electrode material, the electrolyte, and the separator. Summary of the Invention

[0005] Technical issues

[0006] This disclosure provides a composition for forming a coating disposed on any surface of a porous polymer substrate for a separator in an electrochemical device, wherein the composition for forming the coating is capable of forming a thin coating because it includes polyacrylic acid (PAA) with a weight-average molecular weight of 200,000 g / mol or greater and 500,000 g / mol or less as a dispersant.

[0007] Furthermore, this disclosure provides a method for manufacturing a separator for an electrochemical device, wherein a coating having a thickness of 1.3 μm or less can be formed by using a composition for forming a coating.

[0008] Technical solution

[0009] To address the aforementioned problems, this disclosure provides a composition for forming a coating, comprising inorganic particles, a binder, a solvent, and a dispersant, wherein the dispersant comprises polyacrylic acid (PAA) with a weight-average molecular weight of about 200,000 g / mol to 500,000 g / mol, and the content of the dispersant is about 1 part by weight to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles.

[0010] In the composition used to form the coating, the viscosity, measured at a temperature of 25°C and a shear rate of 10 rpm, can be from about 5 cp to 30 cp.

[0011] The average particle size (D) of the solids in the composition used to form the coating 50 The diameter can range from approximately 1 μm to 1.5 μm.

[0012] The solids content of the composition used to form the coating may be from about 30% to 35% by weight.

[0013] The content of inorganic particles may be from about 80 parts by weight to 99 parts by weight relative to the total solids of 100 parts by weight of the composition used to form the coating.

[0014] The content of the binder may be from about 0.5 parts by weight to 10 parts by weight relative to the total solids of 100 parts by weight of the composition used to form the coating.

[0015] This disclosure provides a method for manufacturing a separator for an electrochemical device, the method comprising applying a composition for forming a coating to at least one surface of a porous polymer substrate, and forming a coating by drying the composition for forming the coating, wherein the composition for forming the coating is applied at a rate of about 3 mpm to 10 mpm when the composition for forming the coating is applied.

[0016] In the step of applying the composition for forming the coating, the porous polymer substrate can be driven at a speed of about 10 mpm to 50 mpm.

[0017] In the coating formation step, the composition used to form the coating may be dried at a temperature of about 50°C to 70°C.

[0018] Prior to the step of applying the composition for forming the coating, a step of preparing the composition for forming the coating may be further included.

[0019] This disclosure provides a separator for an electrochemical device, the separator comprising a porous polymer substrate and a coating disposed on at least one surface of the porous polymer substrate, wherein the coating comprises inorganic particles, a binder, and a dispersant, the dispersant comprising polyacrylic acid (PAA) having a weight-average molecular weight of about 200,000 g / mol or greater and 500,000 g / mol or less, the dispersant content being about 1 part by weight or more and 5 parts by weight or less relative to the total weight of 100 parts by weight of inorganic particles, and the coating thickness being about 1.3 μm or less.

[0020] Technical effect

[0021] The composition for forming a coating according to this disclosure contains polyacrylic acid (PAA) having a weight-average molecular weight of about 200,000 g / mol to 500,000 g / mol as a dispersant, and therefore has the advantage of being able to form a thin film coating.

[0022] Furthermore, the method for manufacturing a separator for an electrochemical device according to the present disclosure has the advantage that the separator for an electrochemical device can be manufactured by coating a composition for forming a coating on a porous polymer substrate at a speed of about 3 mpm or higher and 10 mpm or less, wherein a coating having a thickness of 1.3 μm or less is provided on at least one surface of the porous polymer substrate. Attached Figure Description

[0023] The following accompanying drawings illustrate preferred embodiments of the present disclosure and, together with the detailed description of the present disclosure described below, are intended to further enhance the understanding of the technical spirit of the present disclosure; therefore, the present disclosure should not be construed as being limited to the matters described in such drawings.

[0024] Figure 1 This is a flowchart illustrating a method for manufacturing a separator for an electrochemical device according to one embodiment of the present disclosure. Detailed Implementation

[0025] Each part of this disclosure will be described in more detail below, enabling those skilled in the art to readily implement it. However, this is merely illustrative, and the scope of this disclosure is not limited to the following.

[0026] In this specification, the term "comprising" is used to list materials, compositions, apparatus, and methods that can be used in this disclosure, but is not limited to the examples listed.

[0027] In this specification, inherent manufacturing and material tolerances are taken into account, and terms such as “about” and “substantially” are used to indicate the range of numerical values ​​or their degree or approximation, and to prevent unfair use of the disclosed content by infringers, wherein precise or absolute diagrams are provided to aid in understanding this disclosure.

[0028] In this specification, when a component is referred to as being "on" another component, this does not preclude other components being disposed between them, but rather means that other components may be disposed further, unless otherwise specifically stated otherwise.

[0029] In this specification, "electrochemical device" may refer to a primary battery, a secondary battery, or a supercapacitor. For example, an electrochemical device may be a lithium-ion secondary battery, and depending on its shape, it may be pouch-shaped, cylindrical, prismatic, or coin-shaped, but the shape of a lithium-ion secondary battery is not limited to these.

[0030] In this specification, "electrode" refers to both "positive electrode" and "negative electrode," and can mean an electrode active material applied to at least one surface of a conductive material without causing a chemical change in the electrochemical device, and then dried. The types of materials and electrode active materials are not limited, as long as they are suitable for use in the electrochemical device.

[0031] In this specification, "separator" generally refers to a functional separator in which a porous coating containing inorganic particles and a binder is formed on at least one surface of a porous polymer substrate, such as a polyolefin substrate or a nonwoven fabric. Furthermore, the separator has porous properties including a large number of pores and acts as a porous ion-conducting barrier, which blocks the electrical contact between the negative and positive electrodes in an electrochemical device while allowing ions to pass through.

[0032] In this specification, porous or having the characteristic of pores means that an object comprises multiple voids or pores, and the voids or pores are connected to each other to form a structure that allows gaseous and / or liquid fluids to pass from one side of the object to the other side.

[0033] In this specification, "porous polymer substrate" can refer to a porous membrane in which multiple pores are formed, which is a substrate that prevents electrical short circuits between the positive and negative electrodes through electrical insulation. For example, when the electrochemical device is a lithium secondary battery, the porous polymer substrate can serve as an ion conduction barrier, blocking electrical contact between the positive and negative electrodes while allowing lithium ions to pass through. At least a portion of the pores can form a three-dimensional network through which the surface of the porous polymer substrate communicates with the interior, allowing fluid to pass through the porous polymer substrate via the pores.

[0034] In this specification, the particle's "average diameter (D)" is used. 50The average diameter (D) refers to the particle diameter at the point corresponding to 50% of the cumulative volume in the volume-based particle size distribution of the target particle. The average diameter can be measured using a laser diffraction method. For example, after dispersing the powder to be measured in a dispersion medium, the powder is introduced into a commercially available laser diffraction particle size measurement device (e.g., Mastersizer 3000), and the particle size distribution is calculated based on the differences in the particle size measurement diffraction pattern as the particles pass through the laser beam. 50 The particle diameter can be measured by calculating the particle diameter at the point corresponding to 50% of the cumulative distribution of particle number based on the diameter in the measuring device.

[0035] In this specification, "average particle size (D)" 50 "(average particle size)" refers to the average particle size of solids contained in a slurry, such as a composition used to form a coating. For example, the average particle size of solids in a composition used to form a coating refers to the average distribution of the sizes of all particles (such as inorganic particles, binders, and dispersants) contained in the composition used to form a coating, and can be measured by the same method as the average diameter of the particles.

[0036] In components of an electrochemical device, a separator may comprise a polymer substrate having a porous structure located between the positive and negative electrodes. The separator prevents electrical short circuits between the positive and negative electrodes by separating the two electrodes while simultaneously allowing electrolytes and ions to pass through. Although the separator itself does not participate in the electrochemical reaction, physical properties such as wettability to the electrolyte, porosity, and thermal shrinkage can affect the performance and safety of the electrochemical device.

[0037] Therefore, various methods have been explored to enhance these physical properties of the separator, including adding coatings to a porous polymer substrate and incorporating various materials into the coating to improve its properties. For example, to improve the mechanical strength of the separator, inorganic substances can be added to the coating, or inorganic substances or hydrates used to improve the flame retardancy and heat resistance of the polymer substrate can be added to the coating.

[0038] Within the coating, inorganic particles can be bonded to other inorganic particles via a polymer binder to form an interstitial volume, through which lithium ions can move. The coating, containing both polymer binder and inorganic particles, facilitates the movement of lithium ions through the separator while simultaneously preventing thermal shrinkage of the separator.

[0039] Meanwhile, when a thick coating is applied to a porous polymer substrate to mitigate the thermal shrinkage problem of the separator, lithium ions may not pass through the separator smoothly because the porosity of the coating is relatively low compared to the porous polymer substrate. Therefore, the resistance of the separator may increase. Furthermore, when the coating thickness is large, the volume of the electrodes and electrode active materials within the confined electrochemical device inevitably decreases. Consequently, a decrease in the energy density of the electrochemical device also exists. Therefore, there is a growing demand for thin coatings that minimize the thermal shrinkage problem of the porous polymer substrate. As a method for designing separators for electrochemical devices incorporating such coatings, compositions capable of forming thin films for coating formation and coating formation methods using the same are actively being researched. For example, to produce such thin film coatings, the compositions used to form the coating need to have excellent dispersibility.

[0040] In view of these points, this disclosure provides a novel composition for forming a thin film coating and a method for manufacturing a separator for an electrochemical device using the same.

[0041] This disclosure will be described in more detail below.

[0042] According to one embodiment of the present disclosure, a separator for an electrochemical device (electrochemical device separator) includes a porous polymer substrate and a coating disposed on at least one surface of the porous polymer substrate and including a polymer binder and inorganic particles.

[0043] This disclosure provides a composition for forming a coating (coating forming composition) for producing a coating in an electrochemical device separator comprising a porous polymer substrate and a coating. In the electrochemical device separator, the coating produced by the coating forming composition can be disposed on one or both surfaces of the porous polymer substrate.

[0044] According to one embodiment of this disclosure, the composition for forming the coating comprises inorganic particles, a binder, a solvent, and a dispersant. The dispersant comprises polyacrylic acid (PAA) with a weight-average molecular weight of about 200,000 g / mol to 500,000 g / mol. The content of the dispersant is about 1 part by weight to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles.

[0045] In compositions used to form coatings, polyacrylic acid (PAA) with a weight-average molecular weight of about 200,000 g / mol to 500,000 g / mol is included as a dispersant, allowing the dispersant to be effectively adsorbed onto the surface of inorganic particles. For example, the weight-average molecular weight of PAA can be about 200,000 g / mol or higher, about 250,000 g / mol or higher, about 300,000 g / mol or higher, or about 350,000 g / mol or higher, and can be about 500,000 g / mol or lower, about 450,000 g / mol or lower, about 400,000 g / mol or lower, or about 350,000 g / mol or lower. When the weight-average molecular weight of PAA meets the above ranges, the high molecular weight allows the long-chain dispersant to adsorb onto a large number of inorganic particles. Therefore, due to steric hindrance, the electrostatic repulsion between the large number of inorganic particles adsorbed by the dispersant can be high. Consequently, the composition for forming the coating, with reduced agglomeration among the inorganic particles, can exhibit excellent dispersion stability. Therefore, when the composition for forming the coating, possessing excellent dispersion stability, is applied at a relatively low coating rate, a coating in the form of a thin film can be formed. When the weight-average molecular weight of the polyacrylic acid dispersant is maintained within the aforementioned range, the dispersion effect and dispersion stability of the composition for forming the coating can be excellent, and a thin film of the coating can be easily formed. Furthermore, the viscosity of the composition for forming the coating can be sufficiently low; therefore, a coating can be formed by using a composition for forming the coating with high dispersion stability.

[0046] Furthermore, when the polyacrylic acid dispersant is in a negatively charged state in the composition used to form the coating, it is adsorbed onto the inorganic particles, thereby improving the dispersion stability of the composition used to form the coating. Therefore, compared with dispersants having the same weight-average molecular weight, the composition used to form the coating is more conducive to forming a thin film of the coating.

[0047] The content of the dispersant relative to the total weight of 100 parts by weight of inorganic particles can be from about 1 part by weight to 5 parts by weight. For example, the content of the dispersant relative to the total weight of 100 parts by weight of inorganic particles can be about 1 part by weight or more, about 1.5 parts by weight or more, about 2 parts by weight or more, or about 2.5 parts by weight or more, and can be about 5 parts by weight or less, about 4.5 parts by weight or less, about 4 parts by weight or less, about 3.5 parts by weight or less, or about 3 parts by weight or less. When the content of the dispersant meets the above range, the dispersant is sufficiently present in the composition used to form the coating, and as described above, the dispersant can be adsorbed onto a large number of inorganic particles. Therefore, the dispersion stability of the composition used to form the coating can be excellent. When the content of the dispersant meets the above range, the dispersant is sufficiently supplied to the composition used to form the coating, thereby preventing an increase in agglomeration between inorganic particles. Therefore, the dispersion stability of the composition used to form the coating can be excellent. Furthermore, when the content of the dispersant meets the above range, an increase in agglomeration between dispersants that may occur due to excessive dispersant can be prevented. Therefore, the viscosity of the composition used to form the coating can be kept sufficiently low.

[0048] According to one embodiment of this disclosure, the composition for forming the coating may have a viscosity of about 5 cp to 30 cp, measured at a temperature of 25°C and a shear rate of 10 rpm. For example, the viscosity of the composition for forming the coating, measured at a temperature of 25°C and a shear rate of 10 rpm, may be about 5 cp or greater, about 10 cp or greater, about 11 cp or greater, about 12 cp or greater, about 13 cp or greater, about 14 cp or greater, or about 15 cp or greater, and may be about 30 cp or less, about 25 cp or less, about 20 cp or less, or about 15 cp or less. The composition for forming the coating is a non-Newtonian fluid and exhibits so-called dilatant flow, wherein the shear stress increases with increasing shear rate. Therefore, the viscosity can vary depending on the temperature and shear rate. When the viscosity measured at 25°C and a shear rate of 10 rpm meets the above-mentioned range, the composition for forming the coating exhibits good flowability at 25°C (the application temperature of the composition for forming the coating). Therefore, the composition for forming the coating facilitates the application of a coating with a uniform and thin thickness onto a porous polymer substrate. Furthermore, when the viscosity of the composition for forming the coating meets the above-mentioned range, the drying process of the composition for forming the coating can be easily performed, and the manufacturing process of the separator for the electrochemical device can be shortened. Therefore, the economic efficiency of this method can be excellent.

[0049] According to one embodiment of this disclosure, the average particle size (D) of the solids in the composition used to form the coating is...50 The average particle size can be from about 1 μm to 1.5 μm. For example, the average particle size of the solids in the composition used to form the coating can be about 1 μm or larger, about 1.1 μm or larger, about 1.2 μm or larger, about 1.3 μm or larger, or about 1.4 μm or larger, and can be about 1.5 μm or smaller, about 1.4 μm or smaller, or about 1.3 μm or smaller. When the average particle size of the solids in the composition used to form the coating meets the above range, the average specific surface area of ​​the particles (e.g., inorganic particles, binders, and dispersants) in the composition used to form the coating can also be high, and therefore, the interaction between particles can be increased. Then, the dispersion stability of the composition used to form the coating can be excellent. Therefore, the coating processability of the composition used to form the coating can be excellent, and a coating with a uniform and thin thickness can be easily formed during the coating process. In addition, when the average particle size meets the above range, particle settling can be effectively prevented compared to the case of excessively large particle size.

[0050] According to one embodiment of this disclosure, the solid content of the composition used to form the coating can be from about 30% to 35% by weight. For example, the solid content of the composition used to form the coating can be about 30% by weight or higher, about 31% by weight or higher, or about 32% by weight or higher, and can be about 35% by weight or lower, about 34% by weight or lower, or about 33% by weight or lower. When the solid content of the composition used to form the coating meets the above range, the viscosity of the composition used to form the coating can meet the above range, so a thin film of the coating is easily formed. Furthermore, as described above, the drying process of the composition used to form the coating can be easily performed, and the manufacturing process of the separator for the electrochemical device can be shortened, and therefore, the economic efficiency of the process can be excellent.

[0051] According to one embodiment of this disclosure, the solvent content in the composition for forming the coating can be from about 60% to 80% by weight. When the solvent content meets the above range, the composition for forming the coating can have a viscosity within the above range, and therefore it is beneficial to form a thin film of the coating. Furthermore, the composition for forming the coating is easy to dry, and the manufacturing process of the separator for the electrochemical device can be shortened. Therefore, the economic efficiency of this method can be excellent. Meanwhile, the solvent can be an aqueous solvent, and the aqueous solvent can be at least one selected from polar solvents such as water, methanol, ethanol, ethylene glycol, diethylene glycol, and glycerol. When using an aqueous solvent, in addition to the advantages of eco-friendliness, there is also the advantage of simplified facilities compared to the use of organic solvents.

[0052] According to one embodiment of this disclosure, the content of inorganic particles may be from about 80 parts by weight to 99 parts by weight relative to 100 parts by weight of the total solids of the composition used to form the coating. For example, the content of inorganic particles may be about 80 parts by weight or more, about 85 parts by weight or more, about 90 parts by weight or more, or about 95 parts by weight or more relative to 100 parts by weight of the total solids of the composition used to form the coating, and may be about 99 parts by weight or less, about 98 parts by weight or less, about 97 parts by weight or less, about 96 parts by weight or less, about 95 parts by weight or less, about 94 parts by weight or less, about 93 parts by weight or less, about 92 parts by weight or less, about 91 parts by weight or less, or about 90 parts by weight or less. When the content of inorganic particles meets the above ranges, the inorganic particles can be sufficiently included in the coating prepared from the composition used to form the coating, thereby minimizing the thermal shrinkage problem of the porous polymer substrate in the electrochemical device separator.

[0053] According to one embodiment of this disclosure, the inorganic particles may be selected from alumina (Al2O3), boehmite (AlO(OH)), BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3(PLZT, 0) <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 The inorganic particles are at least one of the following: PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), tin-zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), and antimony pentoxide (Sb2O5). For example, the inorganic particles may be alumina. The inorganic particles may not undergo oxidation and / or reduction reactions within the operating voltage range of the electrochemical device (e.g., 0V to 5V based on Li / Li⁺). When the composition used to form the coating and the coating formed therefrom include the aforementioned inorganic particles, the thermal shrinkage problem of the electrochemical device partition can be effectively improved due to the high heat resistance of the aforementioned inorganic particles.

[0054] According to one embodiment of this disclosure, the binder content can be from about 0.5 parts by weight to 10 parts by weight relative to 100 parts by weight of the total solids of the composition used to form the coating. For example, the binder content can be about 0.5 parts by weight or more, about 1 part by weight or more, about 1.5 parts by weight or more, or about 2 parts by weight or more relative to 100 parts by weight of the total solids of the composition used to form the coating, and can be about 10 parts by weight or less, about 9 parts by weight or less, about 8 parts by weight or less, about 7 parts by weight or less, about 6 parts by weight or less, or about 5 parts by weight or less. When the binder content meets the above ranges, the interstitial volume formed by the inorganic particles interconnected by the binder can be effectively increased. As a result, the porosity of the final coating can be high. Furthermore, since the inorganic particles are fixed by the binder, the porosity of the coating can be stably maintained even during long-term operation of the electrochemical device. In addition, the adhesion strength between the coating and the electrode can also be improved by the binder.

[0055] According to one embodiment of this disclosure, the adhesive may be selected from polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, polyvinyl-co-vinyl acetate, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullullan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullullan, and carboxymethyl cellulose. The adhesive comprises at least one of methylcellulose, acrylonitrile-styrene-butadiene copolymer, polyimide, and styrene-butadiene rubber. When the composition used to form the coating and the coating formed therefrom include the above-mentioned adhesive, the separator used in the electrochemical device can have excellent adhesion strength to the electrode due to the high adhesion strength of the above-mentioned adhesive.

[0056] This disclosure provides a method for manufacturing a separator in an electrochemical device.

[0057] In a method for manufacturing a separator in an electrochemical device, a composition for forming a coating is used. For example, the method includes the step of forming a coating on at least one surface of a porous polymer substrate using the composition for forming a coating. In a method for manufacturing a separator in an electrochemical device according to one embodiment of this disclosure, descriptions of the composition for forming a coating will be omitted.

[0058] Reference Figure 1 This disclosure will be described in more detail.

[0059] A method for manufacturing an electrochemical device separator according to one embodiment of the present disclosure includes: a step (S20) of applying a composition for forming a coating to at least one surface of a porous polymer substrate; and a step (S30) of forming a coating by drying the composition for forming a coating. In the step (S20) of applying the composition for forming a coating, the composition for forming a coating may be applied at a rate of about 3 mpm to 10 mpm.

[0060] According to one embodiment of this disclosure, the method for manufacturing an electrochemical device separator may further include a step (S10) of preparing a composition for forming a coating. In step (S10) of preparing the composition for forming a coating, inorganic particles, a binder, a dispersant, and a surfactant may be prepared. The prepared inorganic particles, binder, dispersant, and surfactant may be added to, for example, ultrapure distilled water (DIW) in a predetermined weight ratio. The inorganic particles may then be pulverized and dispersed to prepare the composition for forming a coating.

[0061] The composition application step (S20) is a step of applying the composition for forming the coating to at least one surface of the porous polymer substrate, and in this step, the composition for forming the coating can be applied by various methods, such as bar coating, dip coating, die coating, roll coating, comma coating, or a combination thereof. For example, in the step of applying the composition for forming the coating (S20), the composition for forming the coating can be applied to at least one surface of the porous polymer substrate by bar coating at a speed of about 3 mpm (meters per minute) to 10 mpm. For example, in step (S20) of applying the composition for forming the coating, the composition for forming the coating can be applied to the porous polymer substrate at a speed of about 3 mpm or greater, 4 mpm or greater, 5 mpm or greater, or 6 mpm or greater, and can also be applied to the porous polymer substrate at a speed of about 10 mpm or less, about 9 mpm or less, about 8 mpm or less, about 7 mpm or less, about 6 mpm or less, about 5 mpm or less, or about 4 mpm or less. Because the composition for forming the coating has shear thickening properties, depending on the application speed of the composition for forming the coating, a thin film may be formed, or it may be difficult to form the coating itself. In this disclosure, when the composition for forming the coating is applied to a surface of the porous polymer substrate at the aforementioned speeds, the composition for forming the coating, which has shear thickening properties, can be smoothly applied to a surface of the porous polymer substrate, and thus a coating with a uniform and thin thickness can be formed. When the coating speed of the composition used to form the coating falls within the above-mentioned range, a thin film coating can be easily formed while maintaining the economic efficiency of the process. Furthermore, when the coating speed of the composition used to form the coating falls within the above-mentioned range, the coating thickness can be maintained at a thin level, and due to the shear thickening properties of the composition used to form the coating, a coating with a uniform thickness can be applied.

[0062] According to one embodiment of this disclosure, in step (S20) of applying the composition for forming a coating, the composition for forming a coating can be applied at a temperature of about 20°C to 30°C. For example, in step (S20) of applying the composition, the composition for forming a coating can be applied at a temperature of about 20°C or higher, 22.5°C or higher, or about 25°C or higher, and can also be applied at a temperature of about 30°C or lower, about 27.5°C or lower, or about 25°C or lower. When the composition for forming a coating is applied within the above temperature range, the viscosity of the composition for forming a coating can meet the above range, thus improving the flowability of the composition for forming a coating. Then, a uniform thin film coating can be easily formed.

[0063] According to one embodiment of this disclosure, in the step (S20) of applying the composition for forming the coating, the porous polymer substrate can be driven at a speed of about 10 mpm to 50 mpm. For example, the driving speed of the porous polymer substrate can be about 10 mpm or more, about 20 mpm or more, or about 30 mpm or more, and can be about 50 mpm or less, about 40 mpm or less, or about 30 mpm or less. When the porous polymer substrate is driven at the above-mentioned speed, the productivity of the porous polymer substrate can be improved compared to the case where the driving speed is too slow. Furthermore, when the porous polymer substrate is driven at the above-mentioned speed, compared to the case where the driving speed is too fast, the coating can be applied to one or both surfaces of the porous polymer substrate with a uniform and thin thickness.

[0064] In step (S30) of forming a coating by drying the composition for forming the coating, the composition for forming the coating applied to at least one surface of the porous polymer substrate in the composition application step (S20) can be dried, so that a coating can be formed on at least one surface of the porous polymer substrate. During drying in the coating forming step (S30), the solvent present in the composition for forming the coating can be removed, so that a thin film containing inorganic particles, binders, dispersants, etc., can be formed.

[0065] According to one embodiment of this disclosure, in the coating formation step (S30), the composition used to form the coating can be dried at a temperature of about 50°C to 70°C. For example, the drying temperature can be about 50°C or higher, about 55°C or higher, or about 60°C or higher, and can be about 70°C or lower, about 65°C or lower, or about 60°C or lower. When the drying temperature in the coating formation step (S30) meets the above range, the solvent can be sufficiently removed, and thus a coating can be formed while being fixed to one surface of the porous polymer substrate. Furthermore, since the heat applied to the composition used to form the coating is relatively low, there is an advantage that the materials included in the coating (such as inorganic particles, binders, and dispersants) and the porous polymer substrate undergo less thermal deformation.

[0066] In the coating forming step (S30), the composition used to form the coating may be dried for about 10 seconds to 10 minutes. For example, in the coating forming step (S30), the drying time may be about 10 seconds or longer, about 30 seconds or longer, about 1 minute or longer, about 2 minutes or longer, about 3 minutes or longer, or about 4 minutes or longer, and may be about 10 minutes or less, about 5 minutes or less, about 3 minutes or less, about 2 minutes or less, about 1 minute or less, or about 30 seconds or less. When the drying temperature and time in the coating forming step (S30) meet the above ranges, the solvent can be sufficiently removed, and it is also advantageous that the particles included in the coating (e.g., inorganic particles, binders, and dispersants) undergo less thermal deformation.

[0067] This disclosure provides a separator for an electrochemical device.

[0068] The separator for an electrochemical device can be manufactured from the composition described above for forming the coating, and can also be manufactured by the method described above for manufacturing the separator for an electrochemical device. In the separator for an electrochemical device according to one embodiment of the present disclosure, the description of the composition for forming the coating and the method for manufacturing the separator for an electrochemical device will be omitted.

[0069] According to one embodiment of this disclosure, a separator for an electrochemical device comprises a porous polymer substrate and a coating disposed on at least one surface of the porous polymer substrate. The coating comprises inorganic particles, a binder, and a dispersant. The dispersant may contain polyacrylic acid (PAA) with a weight-average molecular weight of 200,000 g / mol to 500,000 g / mol, and the content of the dispersant may be 1 to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles. The thickness of the coating may be 1.3 μm or less.

[0070] According to one embodiment of this disclosure, the coating comprises inorganic particles, a binder, and a dispersant. The dispersant may comprise polyacrylic acid (PAA) with a weight-average molecular weight of about 200,000 g / mol to 500,000 g / mol, and the content of the dispersant may be about 1 part by weight to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles. The thickness of the coating may be about 1.3 μm or less. In a separator for an electrochemical device, the coating comprises a polyacrylic acid dispersant having a weight-average molecular weight of about 200,000 g / mol to 500,000 g / mol, and the content of the dispersant is in the range of about 1 part by weight to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles; therefore, the coating may be a film with a thickness of about 1.3 μm or less.

[0071] For example, the coating thickness can be about 0.5 μm or greater, about 0.6 μm or greater, about 0.7 μm or greater, about 0.8 μm or greater, about 0.9 μm or greater, or about 1 μm or greater, and can be about 1.3 μm or less, about 1.2 μm or less, about 1.1 μm or less, about 1 μm or less, about 0.9 μm or less, or about 0.8 μm or less. When the coating thickness meets the above ranges, lithium ions can pass through the coating more smoothly due to the small coating thickness. Therefore, it is advantageous to have low resistance of the electrochemical device separator. Furthermore, since the total thickness of the electrochemical device separator including the coating can also be small, the electrochemical device including the electrochemical device separator can include a relatively large amount of electrode active material. Therefore, the energy density of the electrochemical device can also be high.

[0072] According to one embodiment of this disclosure, the porosity of the coating can be from about 30% to 60% by volume. For example, the porosity of the coating can be about 30% by volume or higher, about 35% by volume or higher, about 40% by volume or higher, or about 45% by volume or higher, and can be about 60% by volume or lower, about 55% by volume or lower, about 50% by volume or lower, or about 45% by volume or lower. When the porosity of the coating meets the above ranges, lithium ions can move smoothly through the pores because the pores can be sufficiently present in the coating. Therefore, the resistance of the electrochemical device separator can be low. Furthermore, compared to the case where the porosity of the coating is too high and there are too many pores in the coating, the electrochemical device separator of this disclosure can have excellent performance in terms of mechanical strength (such as puncture strength).

[0073] According to one embodiment of this disclosure, the average diameter (D) of the inorganic particles is... 50The diameter of the inorganic particles can range from approximately 300 nm to 800 nm. For example, the average diameter of the inorganic particles can be approximately 300 nm or larger, approximately 400 nm or larger, or approximately 500 nm or larger, and can be approximately 800 nm or smaller, approximately 700 nm or smaller, approximately 600 nm or smaller, or approximately 500 nm or smaller. When the diameter of the inorganic particles meets the above range, sufficient gaps can exist between the inorganic particles filling the coating. Therefore, the porosity and permeability of the coating can be excellent. Therefore, since lithium ions can move smoothly through the coating, the resistance of the separator in the electrochemical device including the coating can be low. Furthermore, when the diameter of the inorganic particles meets the above range, the dispersibility of the inorganic particles within the composition used to form the coating can be excellent, and the resulting coating thickness can also be thin.

[0074] According to one embodiment of this disclosure, the porous polymer substrate can be a porous membrane in which multiple pores are formed, and can prevent electrical short circuits between the positive and negative electrodes through electrical insulation. For example, when the electrochemical device is a lithium secondary battery, the porous polymer substrate can be an ion conduction barrier that blocks electrical contact between the positive and negative electrodes while allowing lithium ions to pass through. At least a portion of the pores can form a three-dimensional network through which the surface of the porous polymer membrane communicates with the interior, and fluid can then pass through the pores into the porous polymer substrate.

[0075] For porous polymer substrates, materials that are physically and chemically stable to electrolytes as organic solvents can be used. For example, porous polymer substrates may include, but are not limited to, resins such as polyolefin-based resins (e.g., polyethylene, polypropylene, and polybutene), polyvinyl chloride, polyethylene terephthalate, polycyclic olefins, polyethersulfone, polyamides, polyimides, polyimide amides, nylon, polytetrafluoroethylene, and copolymers or mixtures thereof. According to one embodiment, polyolefin-based resins may be used. Polyolefin-based resins are suitable for manufacturing electrochemical devices with high energy densities because the resins can be processed to a relatively thin thickness and allow for easy application of compositions for forming coatings.

[0076] Porous polymer substrates can have a single-layer or multi-layer structure. A porous polymer substrate may include two or more polymer resin layers with different melting points (Tm) to provide a shut-off function in the event of high-temperature thermal runaway of the battery. For example, a porous polymer substrate may include a polypropylene layer with a relatively high melting point and a polyethylene layer with a relatively low melting point. According to one embodiment, the porous polymer substrate may have a three-layer structure, wherein polypropylene, polyethylene, and polypropylene are stacked sequentially. The polyethylene layer melts as the battery temperature rises to a predetermined temperature or higher, allowing the pores to close, thereby preventing thermal runaway of the battery.

[0077] According to one embodiment of this disclosure, the thickness of the porous polymer substrate can be from about 6 μm to 15 μm. For example, the thickness of the porous polymer substrate can be about 6 μm or more, about 8 μm or more, or about 10 μm or more, and can be about 15 μm or less, about 13 μm or less, about 11 μm or less, or about 9 μm or less. By controlling the thickness of the porous polymer substrate within the above range, the volume of the electrochemical device can be minimized, while the positive and negative electrodes can be electrically insulated, thereby increasing the amount of active material contained in the electrochemical device.

[0078] According to one embodiment of this disclosure, a porous polymer substrate may include pores with an average diameter of about 0.01 μm to 1 μm. For example, the size of the pores included in the porous polymer substrate may be about 0.01 μm or larger, about 0.02 μm or larger, about 0.03 μm or larger, or about 0.04 μm or larger, and may be about 1 μm or smaller, about 0.09 μm or smaller, about 0.08 μm or smaller, about 0.07 μm or smaller, or about 0.06 μm or smaller. According to one embodiment, the size of the pores may be about 0.02 μm to 0.06 μm. By controlling the pore size of the porous polymer substrate within the above range, the air permeability and ionic conductivity of the entire separator to be manufactured can be controlled.

[0079] The porous polymer substrate may have an air permeability of about 10 s / 100cc to 100 s / 100cc. For example, the air permeability of the porous polymer substrate may be about 10 s / 100cc or higher, about 20 s / 100cc or higher, about 30 s / 100cc or higher, about 40 s / 100cc or higher, or about 50 s / 100cc or higher, and may be about 100 s / 100cc or lower, about 90 s / 100cc or lower, about 80 s / 100cc or lower, about 70 s / 100cc or lower, about 60 s / 100cc or lower, or about 50 s / 100cc or lower. According to one embodiment, the air permeability of the porous polymer substrate may be about 50 s / 100cc to 70 s / 100cc. When the permeability of the porous polymer substrate falls within the above-mentioned range, the permeability of the manufactured separator can be provided within a range suitable for ensuring the output characteristics and cycle characteristics of the electrochemical device.

[0080] Air permeability (s / 100cc) refers to the time (sec) it takes for 100cc of air to pass through a porous polymer substrate or separator with a predetermined area under constant pressure. Air permeability can be measured using an air permeability tester (Gurley air permeability tester) according to ASTM D 726-58, ASTM D726-94, or JIS-P8117. For example, Gurley's 4110 N device can be used to measure 100cc of air at 0.304 kPa or 1.215 kN / m³. 2 Water pressure passing through 1 square inch (or 6.54 cm) 2 The time taken to pass through a sample. For example, Asahi Seiko's EG01-55-1MR instrument can be used to measure the time it takes for 100 cc of air to pass through a 1 square inch sample at room temperature under a constant pressure of 4.8 inches of water column.

[0081] The porous polymer substrate can have a porosity of about 10 vol% to 70 vol%. For example, the porosity of the porous polymer substrate can be about 10 vol% or higher, about 20 vol% or higher, about 30 vol% or higher, or about 40 vol% or higher, and can be about 70 vol% or lower, about 60 vol% or lower, or about 50 vol% or lower. According to one embodiment, the porosity of the porous polymer substrate can be about 40 vol% to 60 vol%. When the porosity of the porous polymer substrate falls within the above range, the ionic conductivity of the manufactured separator can be provided within a range suitable for ensuring the output characteristics and cycle characteristics of the electrochemical device.

[0082] The porosity mentioned above refers to the volume ratio of pores to the total volume in each coating and porous polymer substrate. Porosity can be measured by methods known in the art. For example, the measurement can be performed using the Brunauer-Emmett-Teller (BET) measurement method with nitrogen adsorption, a capillary flow porometer, or a water or mercury immersion method.

[0083] This disclosure provides an electrochemical device.

[0084] Electrochemical devices may include the separators described above for electrochemical devices.

[0085] According to one embodiment of this disclosure, an electrochemical device includes a positive electrode, a negative electrode, and a separator for the electrochemical device, and the separator for the electrochemical device can be inserted between the positive electrode and the negative electrode. In the electrochemical device according to one embodiment of this disclosure, the descriptions that are repeated with the descriptions of the composition for forming the coating, the method for manufacturing the separator of the electrochemical device, and the separator for the electrochemical device will be omitted.

[0086] An electrochemical device is a device that converts chemical energy into electrical energy through an electrochemical reaction, and it includes the concepts of primary batteries and secondary batteries. Secondary batteries are rechargeable and dischargeable, and refer to lithium-ion batteries, nickel-cadmium batteries, nickel-metal hydride batteries, etc. Lithium-ion batteries use lithium ions as ionic conductors. Examples include, but are not limited to, non-aqueous electrolyte secondary batteries containing liquid electrolytes, solid-state batteries containing solid electrolytes, lithium polymer batteries containing gel polymer electrolytes, and lithium metal batteries using lithium metal as the negative electrode.

[0087] Because the electrochemical device includes the separator described above according to the present disclosure, lithium ions can move smoothly through the separator due to the low thickness of the coating. Therefore, it is advantageous to have low resistance and excellent output.

[0088] According to one embodiment of this disclosure, the positive electrode may include: a positive electrode current collector; and a positive electrode active material layer on at least one surface of the current collector, the positive electrode active material layer comprising a positive electrode active material, a conductive material, and a binder resin. The positive electrode active material may include one or a mixture of two or more of the following: layered compounds, such as lithium manganese composite oxides (LiMn2O4, LiMnO2, etc.), lithium cobalt oxides (LiCoO2), and lithium nickel oxides (LiNiO2), or compounds substituted with one or more transition metals; lithium manganese oxides, such as those with the chemical formula Li... 1+x Mn 2-x O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; and LiNi 1-x M x O2 represents Ni-site type lithium nickel oxides (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); LiMn 1-x M x Lithium manganese composite oxides represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4, wherein a portion of the Li in the chemical formula is replaced by an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.

[0089] According to one embodiment of the present disclosure, the negative electrode may include: a negative electrode current collector; and a negative electrode active material layer on at least one surface of the current collector, the negative electrode active material layer including a negative electrode active material, a conductive material, and a binder resin. As the negative electrode active material, the negative electrode may include one type or a mixture of two or more types selected from: lithium metal oxides; carbon, such as non-graphitizable carbon or graphite-based carbon; metal composite oxides, such as Li x Fe2O3(0≤x≤1), Li x WO2(0≤x≤1) and Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, Ge; Me: Al, B, P, Si, elements of Groups 1, 2 and 3 of the periodic table, halogen; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4 and Bi2O5; conductive polymers, such as polyacetylene; Li-Co-Ni based materials; and titanium oxides.

[0090] According to one embodiment of the present disclosure, the conductive material may be any one selected from, for example, graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whiskers, conductive metal oxide, activated carbon and polyphenylene derivatives, or a mixture of two or more types of these conductive materials. According to one embodiment, the conductive material may be one type selected from: natural graphite, artificial graphite, Super P, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium oxide, or a mixture of two or more types of these conductive materials.

[0091] According to one embodiment of the present disclosure, the current collector is not particularly limited as long as it has high electrical conductivity and does not cause chemical changes in the corresponding battery. For example, stainless steel, copper, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel whose surface has been treated with carbon, nickel, titanium, silver or the like may be used.

[0092] According to one embodiment of this disclosure, the adhesive resin can be a polymer commonly used in the art for electrodes. Non-limiting examples of such adhesive resins may include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, and cellulose acetate propionate. Acetatepropionate, cyanoethylpullulan, cyanoethylpolyvinyl alcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, and carboxyl methylcellulose, and are not limited to these.

[0093] According to one embodiment of this disclosure, the cathode slurry used to produce the cathode active material layer may contain a dispersant. The dispersant may be a pyrrolidone-based compound, and specifically, it may be N-methylpyrrolidone (ADC-01, LG Chem).

[0094] According to one embodiment of this disclosure, the electrochemical device may further include an electrolyte. The electrolyte includes components having a composition such as A. + B - Salts with a structure that can dissolve or dissociate in organic solvents, but this disclosure is not limited thereto. + It may include alkali metal cations such as Li + Na + K+ Or ions composed of combinations thereof. Furthermore, B - It may include anions such as PF6 - BF4 - Cl - ,Br - I - ClO4 - AsF6 - CH3CO2 - CF3SO3 - N(CF3SO2)2 - C(CF2SO2)3 - Ions, or combinations thereof. Organic solvents include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone, or mixtures thereof.

[0095] In one embodiment of this disclosure, a battery module comprising a battery including an electrochemical device battery as a unit cell, a battery pack comprising the battery module, and a device comprising the battery pack as a power source may be provided. Specific examples of such a device may include: a power tool powered and driven by an electric motor; an electric vehicle including an electric vehicle (EV), a hybrid electric vehicle (HEV), or a plug-in hybrid electric vehicle (PHEV); an electric two-wheeled vehicle including an electric bicycle (E-bike) or an electric scooter; an electric golf cart; or a power storage system, but are not limited thereto.

[0096] The present disclosure will be described in detail below with reference to embodiments. However, embodiments of the present disclosure can be modified in various different ways, and the scope of the present disclosure is not to be construed as limited to the embodiments described below. The embodiments of this specification are provided to illustrate the present disclosure more completely to those skilled in the art.

[0097] Examples and Comparative Examples

[0098] Preparation of compositions for forming coatings

[0099] <Preparation Example 1>

[0100] Preparation of alumina (AES11, Sumitomo Co., Ltd.) as inorganic particles, particle size (D) 50 The inorganic particles, binder, dispersant, and surfactant were added to 231.6 g of ultrapure distilled water (DIW) at a weight ratio of 95.6:2.5:1:0.9. The inorganic particles were then pulverized and dispersed to prepare a composition for coating formation (solids content 30% by weight). The viscosity of the composition for coating formation (viscosity measurement device: LV model viscometer (using UL adapter), Brookfield) was 13.2 cp, measured at 25 °C and 10 rpm. The average particle size of the solids in the composition for coating formation was also measured. 50 The value is 1.43 μm.

[0101] <Preparation Example 2>

[0102] The composition for forming the coating was prepared in the same manner as in Preparation Example 1, except that the prepared inorganic particles, binder, dispersant, and surfactant were added to 230 g of ultrapure distilled water (DIW) in a weight ratio of 95.1:2.5:1.5:0.9. The inorganic particles were then pulverized and dispersed to prepare the composition for forming the coating (solid content 30% by weight). The viscosity of the composition for forming the coating, measured at 25°C and a shear rate of 10 rpm, was 13.8 cp, and the average particle size (D) of the solids in the composition for forming the coating was... 50 The value is 1.44 μm.

[0103] <Preparation Example 3>

[0104] The composition for forming the coating was prepared in the same manner as in Preparation Example 1, except that the prepared inorganic particles, binder, dispersant, and surfactant were added to 228.5 g of ultrapure distilled water (DIW) in a weight ratio of 94.6:2.5:2:0.9. The inorganic particles were then pulverized and dispersed to prepare the composition for forming the coating (solid content 30% by weight). The viscosity of the composition for forming the coating, measured at 25°C and a shear rate of 10 rpm, was 13.8 cp, and the average particle size (D) of the solids in the composition for forming the coating was... 50 The value is 1.43 μm.

[0105] <Comparative Preparation Example 1>

[0106] The composition for forming the coating was prepared in the same manner as in Preparation Example 1, except that the prepared inorganic particles, binder, dispersant, and surfactant were added to 233.1 g of ultrapure distilled water (DIW) in a weight ratio of 96.1:2.5:0.5:0.9. The inorganic particles were then pulverized and dispersed to prepare the composition for forming the coating (solid content 30% by weight). The viscosity of the composition for forming the coating, measured at 25°C and a shear rate of 10 rpm, was 12.6 cp, and the average particle size (D) of the solids in the composition for forming the coating was... 50 The value is 1.41 μm.

[0107] <Comparative Preparation Example 2>

[0108] The composition for forming the coating was prepared in the same manner as in Preparation Example 1, except that the prepared inorganic particles, binder, dispersant, and surfactant were added to 219.3 g of ultrapure distilled water (DIW) in a weight ratio of 91.6:2.5:5:0.9. The inorganic particles were then pulverized and dispersed to prepare the composition for forming the coating (solid content 30% by weight). The viscosity of the composition for forming the coating, measured at 25°C and a shear rate of 10 rpm, was 30.6 cp, and the average particle size (D) of the solids in the composition for forming the coating was... 50 The value is 1.59 μm.

[0109] <Comparative Preparation Example 3>

[0110] The composition for forming the coating was prepared in the same manner as in Preparation Example 1, except that: polyacrylic acid (CK732, Lubrizol Corporation) with a weight average molecular weight of 6,000 g / mol was prepared as a dispersant; the prepared inorganic particles, binder, dispersant, and surfactant were added to 233.6 g of ultrapure distilled water (DIW) in a weight ratio of 95.6:2.5:1:0.9; and then the inorganic particles were pulverized and dispersed to prepare the composition for forming the coating (solid content 30 wt%). The viscosity of the composition for forming the coating, measured at 25°C and a shear rate of 10 rpm, was 12.0 cp, and the average particle size (D) of the solids in the composition for forming the coating was... 50 The value is 1.87 μm.

[0111] <Comparative Preparation Example 4>

[0112] The composition for forming the coating was prepared in the same manner as in Preparation Example 1, except that: polyacrylic acid with a weight-average molecular weight of 600,000 g / mol was prepared as a dispersant; the prepared inorganic particles, binder, dispersant, and surfactant were added to 215.2 g of ultrapure distilled water (DIW) in a weight ratio of 95.6:2.5:1:0.9; and then the inorganic particles were pulverized and dispersed to prepare the composition for forming the coating (solid content 30 wt%). The viscosity of the composition for forming the coating, measured at 25 °C and a shear rate of 10 rpm, was 57.6 cp, and the average particle size (D) of the solids in the composition for forming the coating was... 50 The value is 1.95 μm.

[0113] Manufacturing of separators for electrochemical devices

[0114] A polyethylene film (thickness: 8.4 μm, air permeability: 62 s / 100cc) was prepared as a porous polymer substrate.

[0115] The porous polymer substrate was moved at a speed of 30 mpm, and the coating composition from the preparation examples and comparative examples was applied to one surface of the porous polymer substrate by a bar coating method. Specifically, the coating composition was applied by a bar coating method at a temperature of 25°C using a doctor blade. Then, while applying the coating composition, the doctor blade coating speed was changed to 1 mpm, 3 mpm, 5 mpm, 7 mpm, 10 mpm, and 20 mpm. Subsequently, the applied coating composition was dried in air at 70°C for 1 minute using a hot air gun, thereby forming a coating on one surface of the porous polymer substrate. Then, a separator for an electrochemical device was completed.

[0116] The properties of the composition used to form the coating and the separator of the electrochemical device are recorded in Table 1 below. The following weight percentages are described based on the weight of the solids in the composition used to form the coating.

[0117] [Table 1]

[0118]

[0119] As shown in Table 1 above, it can be observed that when the compositions for forming coatings of Preparation Examples 1 to 3 are applied at a rate of 3 to 10 mpm, a coating with a thickness of 1.3 μm or less is formed, wherein the composition contains 1.1% to 2.1% by weight of polyacrylic acid (PAA) with a weight average molecular weight of 345,000 g / mol (200,000 g / mol to 500,000 g / mol) as a dispersant relative to 100 parts by weight of inorganic particles. Furthermore, in the case of the composition for forming coatings of Preparation Example 3, it can be observed that an ultrathin film coating with a thickness of 0.81 μm is formed at a coating speed of 3 mpm. Thus, it can be seen that a thin film coating can be formed by using the composition for forming coatings disclosed herein to manufacture a separator for an electrochemical device.

[0120] Meanwhile, it was observed that although the compositions for forming the coating from Preparation Examples 1 to 3 were used, a coating could not be formed at a coating speed of 1 mpm, or the coating thickness exceeded 1.6 μm at a coating speed of 20 mpm. Furthermore, when the composition for forming the coating from Comparative Preparation Example 1 was used, wherein the dispersant content in the composition for forming the coating was 0.5%, a thick coating with a thickness of 3.02 μm to 3.26 μm was formed at the same coating speed (3 mpm to 10 mpm) as in Preparation Examples 1 to 3.

[0121] Furthermore, when the compositions for forming the coating from Comparative Preparation Example 3 and Comparative Preparation Example 4 were used, wherein the weight-average molecular weight of the dispersant was 6,000 g / mol and 600,000 g / mol, respectively, it was found that although the coating speed was the same as that in Preparation Examples 1 to 3, relatively thick coatings were formed, with maximum thicknesses of 1.91 μm and 2.34 μm, respectively.

[0122] Experimental Example

[0123] (1) Measurement of the resistance of the separator

[0124] Electrochemical device separators (Examples 1 to 3) were prepared by applying the coating-forming composition of Preparation Example 3 at rates of 3 mpm, 5 mpm, and 7 mpm, respectively; electrochemical device separators (Comparative Example 1) were prepared by applying the coating-forming composition of Preparation Example 3 at a rate of 20 mpm; electrochemical device separators (Comparative Examples 2 to 4) were prepared by applying the coating-forming composition of Comparative Preparation Example 3 at rates of 3 mpm, 5 mpm, and 7 mpm, respectively; and electrochemical device separators (Comparative Examples 5 to 7) were prepared by applying the coating-forming composition of Comparative Preparation Example 4 at rates of 3 mpm, 5 mpm, and 7 mpm, respectively. Each of these separators was inserted between SUS plates to manufacture a coin cell. An electrolyte containing 1 M LiPF6 in a 1:2 volume ratio of ethylene carbonate to ethyl methyl carbonate was injected into the coin cell. To measure the resistance of the coin cell, the resistance was measured by electrochemical impedance spectroscopy analysis using a Bio-Logic Science Instrument VMP3 at 25°C with an amplitude of 10 mV and a scan range of 0.1 Hz to 1 MHz. The results are recorded in Tables 2 and 3 below.

[0125] (2) Measurement of the wet shrinkage rate of the partition

[0126] The separators of the electrochemical devices of Examples 1 to 3 and Comparative Examples 1 to 7 were prepared as test pieces with a size of 5 cm × 5 cm, and each was inserted into an aluminum bag with a size of 7 cm × 10 cm. Less than 1 g of electrolyte 1 was injected into the above bags, and the bags were sealed. The sealed bags were stored in a convection oven at 135°C for 1 hour, and then the separators were removed. The thermal shrinkage rate in each of the MD and TD directions was calculated according to [(initial length of the test piece - length after storage @ 135°C / 1 h) / (initial length of the test piece)] × 100 (%).

[0127] As the electrolyte, an electrolyte containing 1 mole of lithium salt LiPF6 and 3 moles of vinylene carbonate (VC), 1.5 moles of propane sulpholactone (PS), and 1 mole of ethylene sulfate (ESa) as additives was used in a solvent containing a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a weight ratio of 3 / 7. The results are recorded in Tables 2 and 3 below.

[0128] [Table 2]

[0129]

[0130] [Table 3]

[0131]

[0132] As shown in Tables 2 and 3 above, it can be observed that the electrochemical device separators produced by the compositions for forming the coating and the separator manufacturing method of this disclosure comprise a thin film coating with a thickness of 0.81 μm to 0.95 μm, and therefore have a lower resistance compared to comparative examples that include a thicker coating. Specifically, the resistance in Examples 1 to 3 is at the level of 0.61 Ω to 0.63 Ω, while the resistance in the case of the comparative examples is at the level of 0.84 Ω to 0.97 Ω.

[0133] Furthermore, in Examples 1 to 3, the thickness of the thin film coating was between 0.81 μm and 0.95 μm, and at this thickness level, the thermal shrinkage problem of the porous polymer substrate could be reduced. Therefore, it can be found that the thermal shrinkage rate of the separator is sufficiently low compared to the comparative examples in which the coating thickness is thicker.

[0134] Although the embodiments of this disclosure have been described above with reference to them, those skilled in the art or with ordinary knowledge of the relevant art will understand that various modifications and changes can be made to the various embodiments of this disclosure without departing from the technical scope of the various embodiments described in the claims. Therefore, the technical scope of the various embodiments of this disclosure should not be limited to what is described in the detailed description of the specification, but should be determined by the claims.

Claims

1. A composition for forming a coating, comprising: Inorganic particles, binders, solvents and dispersants, The dispersant comprises polyacrylic acid (PAA) with a weight-average molecular weight of 200,000 g / mol to 500,000 g / mol, and The content of the dispersant is from 1 part by weight to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles.

2. The composition according to claim 1, wherein the viscosity of the composition for forming the coating, measured at a temperature of 25°C and a shear rate of 10 rpm, is between 5 cp and 30 cp.

3. The composition according to claim 1, wherein the average particle size (D) of the solids in the composition for forming the coating 50 The thickness ranges from 1 μm to 1.5 μm.

4. The composition according to claim 1, wherein the solid content of the composition for forming the coating is 30% to 35% by weight.

5. The composition according to claim 1, wherein the content of the inorganic particles is 80 to 99 parts by weight relative to 100 parts by weight of the total solids of the composition for forming the coating.

6. The composition according to claim 1, wherein the content of the adhesive is from about 0.5 parts by weight to 10 parts by weight relative to the total solids of 100 parts by weight of the composition for forming the coating.

7. A method for manufacturing a separator for an electrochemical device, the method comprising: The composition for forming a coating according to claim 1 is applied to at least one surface of a porous polymer substrate; and The coating is formed by drying the composition used to form the coating. When applying the composition for forming the coating, the composition for forming the coating is applied at a rate of 3 mpm to 10 mpm.

8. The method of manufacturing a separator for an electrochemical device according to claim 7, wherein the porous polymer substrate is operated at a speed of 10 mpm to 50 mpm when the composition for forming the coating is applied.

9. The method of manufacturing a separator for an electrochemical device according to claim 7, wherein the composition for forming the coating is dried at a temperature of 50°C to 70°C during the formation of the coating.

10. The method of manufacturing a separator for an electrochemical device according to claim 7, the method further comprising: The composition for forming the coating is prepared prior to application of the composition for forming the coating.

11. A separator for an electrochemical device, the separator comprising: Porous polymer substrate; and A coating disposed on at least one surface of the porous polymer substrate, The coating comprises inorganic particles, binders, and dispersants. The dispersant contains polyacrylic acid (PAA) with a weight-average molecular weight of 200,000 g / mol to 500,000 g / mol, and The content of the dispersant is 1 to 5 parts by weight relative to the total weight of 100 parts by weight of the inorganic particles. The coating thickness is 1.3 μm or less.

Citation Information

Patent Citations

  • Handle for box, manufacturing device and manufacturing method thereof, and box including the same

    KR1020240128230A

  • Organic light emitting device, composition for organic material layer of organic light emitting device and manufacturing method of organic light emitting device

    KR1020250117575A